TRANSAXILLARY AORTIC VALVE REPLACEMENT AS AN ALTERNATIVE TO CURRENT TREATMENT METHODS - Taranowicz, Mateusz; Kowalska, Monika; Ścibisz, Katarzyna; Zdobylak, Dominika; Ollik, Karolina; Harenza, Kamil; Zięba, Anita; Domin, Michał; Całka, Justyna; Kowalczyk, Olga (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and aim: The aortic valve consists of three lobes, often presenting as a bilobed congenital heart defect. It is responsible for the outflow of blood from the left ventricle into the aorta by preventing backflow of blood into the heart during left ventricular diastole. The most common health problems associated with the aortic valve include stenosis and regurgitation. In minor defects, regular pharmacological treatment may be sufficient. In larger defects, these are available and necessary for treatment; they often require a mechanical valve. The aim of this paper is to review the availability of transaxillary access for aortic valve replacement as an emergency treatment method and its compatibility with current alternatives. The advantages and disadvantages of this treatment are highlighted.Materials and Methods: This narrative review was based on a structured analysis of published clinical trials, extension studies, and review articles evaluating, clinical efficacy, complications in patients with surgical methods for aortic stenosis defects.Results: A significant number of people with aortic valve disease can be managed with minimally invasive monitoring and do not require radical treatment. However, if the defect is severe, surgical treatment is necessary. Aortic valve replacement is currently treated using three basic methods. The first is a classic sternotomy, which involves opening the chest by splitting the sternum. The second method is percutaneous valve implantation: TAVI. Recently, thanks to the use of modern equipment, minimally invasive surgical techniques have become available, including: partial upper sternotomy, mini-sternotomy, and right anterior mini-thoracotomy. During surgery, two types of valves can be implanted: mechanical or biological. Each is preferred by different groups of patients and carries different consequences. Therefore, when qualifying for the procedure, it is crucial to consider the patient's preferences, as well as a thorough analysis of the clinical situation by a team of experts.Conclusions: The transaxillary approach is a more invasive method than TAVI, but less invasive than the sternotomy approach. This allows for shorter recovery times after the procedure, with more thorough cleaning and valve adjustment than with TAVI. At the same time, this method requires greater operator dexterity, as access is limited compared to traditional incisions, both in terms of space for instruments and visibility.